(Fe, Mn)Zn13 phase and its core-shell structure in novel biodegradable Zn-Mn-Fe alloys. (15th January 2019) - Shi, Zhang-Zhi; Li, Zi-Lin; Bai, Wen-Shan; Tuoliken, Ayisulu; Yu, Jing; Liu, Xue-Feng
Abstract: Effects of Fe addition on mechanical properties and microstructures of biodegradable Zn-Mn alloys are unknown yet, which will be revealed in the present study. Minor addition of Fe results in formation of (Fe, Mn)Zn13 phase, which can have a (Fe, Mn)Zn13 /MnZn13 core/shell structure. The core and the shell exhibit a coherent orientation relationship (OR). Between them, there exists a thin interlayer with an irrational OR with respect to either the core or the shell. Although the as-cast alloys are very brittle, their ductilities and strengths can be significantly improved through hot rolling, owing to significant grain refinement of Zn matrix and refinement of the second phase particles. Elongation of the hot-rolled Zn-1Mn-0.1Fe alloy is about 4.8 times of that of the hot-rolled Zn-1Mn-0.5Fe alloy, indicating that ductility of Zn-Mn-Fe alloy is very sensitive to Fe content. Graphical abstract: Highlights: Characteristics of (Fe, Mn)Zn13 in Zn alloys are firstly investigated. MnZn13 epitaxially grows on (Fe, Mn)Zn13 resulting in a core/shell structure. Orientation relationships related to the core/shell structure are identified. Mechanical properties of the alloys are significantly improved through hot rolling.